Developing a wind turbine planning platform: Integration of "sound propagation model–GIS-game engine" triplet. (September 2017) - Rafiee, Azarakhsh; Van der Male, Pim; Dias, Eduardo; Scholten, Henk
Abstract: In this study, we propose an interactive information system for wind turbine siting, considering its visual and sound externalities. This system is an integration of game engine, GIS and analytical sound propagation model in a unified 3D web environment. The game engine–GIS integration provides a 3D virtual environment where users can navigate through the existing geospatial data of the whole country and place different wind turbine types to explore their visual impact on the landscape. The integration of a sound propagation model in the game engine–GIS supports the real-time calculation and feedback regarding wind turbine sound at the surrounding buildings. The platform's GIS component enables massive (on-the-fly) georeferenced data utilization through tiling techniques as well as data accessibility and interoperability via cloud-based architecture and open geospatial standard protocols. The game engine, on the other hand, supports performance optimization for both data display and sound model calculations. Graphical abstract: Highlights: We developed a 3D interactive wind turbine scenario planning. This system integrates game engine, GIS and sound propagation model. Game engine capabilities boosted visualization as well as sound model performance. Embedding GIS techniques enabled serving massive datasets from different resources. Sound model integration with game engine and GIS enabled real-time sound analysis.